The Contribution of Non-Professional Antigen-Presenting Cells to Immunity and Tolerance in the Liver - Mehrfeld, Christina; Zenner, Steven; Kornek, Miroslaw; Lukacs-Kornek, Veronika (Frontiers in Immunology, 2018)
The liver represents a unique organ biased towards a tolerogenic milieu. Due to its anatomical location, it is constantly exposed to microbial and food-derived antigens from the gut and thus equipped with a complex cellular network that ensures dampening T-cell responses. Within this cellular network, parenchymal (hepatocytes), non-parenchymal cells (liver sinusoidal endothelial cells, LSECs, hepatic stellate cells HSCs) and immune cells contribute directly or indirectly to this process. Despite of this refractory bias the liver is capable of mounting efficient T-cell responses. How the various antigen presenting cell (APC) populations contribute to this process and how they handle danger signals determine the outcome of the generated immune responses. Importantly, liver mounted responses convey consequences not only for the local but to systemic immunity. Here we discuss the various aspects of antigen presentation and its consequences by the non-professional APCs in the liver microenvironment.